2013
DOI: 10.2215/cjn.08230811
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of the Iron-Based Phosphate Binder PA21 in Hemodialysis Patients

Abstract: SummaryBackground and objectives A dose-finding study was undertaken to investigate the efficacy of PA21, a novel polynuclear iron(III)-oxyhydroxide phosphate binder.Design, setting, participants, & measurements In a randomized, active-controlled, multicenter, open-label study at 50 clinical sites in Europe and the United States, hemodialysis patients were randomized to PA21 at dosages of 1.25, 5.0, 7.5, 10.0, or 12.5 g/d or sevelamer-HCl 4.8 g/d for 6 weeks. The primary efficacy endpoint was the change in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 10 publications
5
61
0
Order By: Relevance
“…The remaining 18 full-text articles were reviewed for more detailed assessment, and 10 studies were excluded because of duplicate reports. Finally, 8 studies [15][16][17][18][19][20][21][22] with 2018 participants met our inclusion criteria and were included in our meta-analysis. The selection process for studies included in the systematic review is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining 18 full-text articles were reviewed for more detailed assessment, and 10 studies were excluded because of duplicate reports. Finally, 8 studies [15][16][17][18][19][20][21][22] with 2018 participants met our inclusion criteria and were included in our meta-analysis. The selection process for studies included in the systematic review is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [15][16][17][18][19]21,22 were parallel randomized controlled trials, while one study 20 was cross-over randomized controlled trial. Three studies 17,18,22 compared iron-based phosphate binders with placebo, four studies 16,17,19,21 made comparison between iron-based phosphate binders and sevelamer, and one study 20 compared ferric citrate with calcium carbonate. Of the eight included trials, five 15,17,[20][21][22] were conducted in Asia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations